A detailed clinical study of pain in 1957 participants with early/moderate Parkinson's disease. (November 2018) - Silverdale, Monty A.; Kobylecki, Christopher; Kass-Iliyya, Lewis; Martinez-Martin, Pablo; Lawton, Michael; Cotterill, Sarah; Chaudhuri, K. Ray; Morris, Huw; Baig, Fahd; Williams, Nigel; Hubbard, Leon; Hu, Michele T.; et al.
Abstract: Introduction: The causes of pain in early/moderate Parkinson's disease (PD) are not well understood. Although peripheral factors such as rigidity, reduced joint movements and poor posture may contribute towards the development of pain, central mechanisms including altered nociceptive processing may also be involved. Methods: We performed a large clinical study to investigate potential factors contributing towards pain in early/moderate PD. We recruited 1957 PD participants who had detailed assessments of pain, motor and non-motor symptoms. The King's Parkinson's Pain scale was used to quantify different subtypes of pain. Results: 85% of participants reported pain (42% with moderate to severe pain). Pain influenced quality of life more than motor symptoms in a multiple regression model. Factors predicting overall pain severity included affective symptoms, autonomic symptoms, motor complications, female gender and younger age, but not motor impairment or disease duration. There was negligible correlation between the severity of motor impairment and the severity of musculoskeletal or dystonic pain as well as between the severity of OFF period motor problems and the severity of OFF period pain or OFF period dystonic pain. Features of central sensitization, including allodynia and altered pain sensation were common in this population. The use of drugs targeting central pain was very low. Conclusions: Pain in early/moderate PD cannot be explained by peripheral factors. Central causes may play a much more important role than previously considered. These results should lead to a major shift in the investigation and management of this common and disabling symptom. Highlights: Pain is common in early/moderate PD and impairs quality of life more than motor symptoms No correlation between mobility problems and musculoskeletal or radicular pain in early/moderate PD No correlation between OFF motor symptoms and OFF period pain in early/moderate PD Features of central pain sensitization are common in early/moderate PD Central factors are a more important cause of pain in early/moderate PD than previously considered